1982
DOI: 10.1210/jcem-55-5-840
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ageing on Glucose Homeostasis*

Abstract: The mechanism of age-related glucose intolerance was investigated by comparing forearm glucose uptake (FGU) during 100-g oral glucose tolerance tests (GTTs) in healthy men of different ages: group Y, 19-24 yr (n = 11); group M, 30-45 yr (n = 12); and group E, 70-83 yr (n = 9).Progressive elevation of the glucose tolerance curve occurred with increasing age, the curve of each group differing from the others at all points from 60-180 min. Although with age absolute levels of FGU were not reduced, the rise in FGU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
2
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 24 publications
7
66
2
1
Order By: Relevance
“…This study is in agreement with other studies where several insulin doses were employed Fink et al, 1983). In addition, studies using various techniques, including the hyperglycemic clamp Elahi et al, 1993), the forearm glucose uptake technique (Jackson et al, 1982) and Min Mod (Chen et al, 1985) have revealed resistance to insulin-induced glucose disposal in aged volunteers. It is obvious that in addition to age various factors in¯uence insulin sensitivity including fat mass, fat distribution, physical ®tness, dietary composition and genetic factors.…”
Section: Effect Of Age On Peripheral Tissue Glucose Utilizationsupporting
confidence: 91%
“…This study is in agreement with other studies where several insulin doses were employed Fink et al, 1983). In addition, studies using various techniques, including the hyperglycemic clamp Elahi et al, 1993), the forearm glucose uptake technique (Jackson et al, 1982) and Min Mod (Chen et al, 1985) have revealed resistance to insulin-induced glucose disposal in aged volunteers. It is obvious that in addition to age various factors in¯uence insulin sensitivity including fat mass, fat distribution, physical ®tness, dietary composition and genetic factors.…”
Section: Effect Of Age On Peripheral Tissue Glucose Utilizationsupporting
confidence: 91%
“…In this context, the impairment of glucose tolerance with aging has been confirmed by numerous previous studies indicating that this decline in glucose tolerance, which begins in the third decade, continues throughout adulthood (11,24,25). These age-related changes particularly characterize the impaired response to glucose challenge rather than FPG, partly due to physical inactivity (26) and potentially associated with a decrease in muscle mass.…”
Section: Variables Related To 2-h Postload Plasma Glucosementioning
confidence: 56%
“…These age-related changes particularly characterize the impaired response to glucose challenge rather than FPG, partly due to physical inactivity (26) and potentially associated with a decrease in muscle mass. In more recent estimations based on arterialized venous plasma, the age-related increase in glucose concentrations from 60 to 180 min after a 100-g oral glucose load averaged 13-14 mg/dl per decade (25). These reports agreed with our results, which showed a mean increase of 9.4 mg/dl per decade between the ages of 30 and 78 years (r ϭ 0.68, P Ͻ 0.0001) in the values for 2-h PG at FPG 126 mg/dl.…”
Section: Variables Related To 2-h Postload Plasma Glucosementioning
confidence: 99%
“…Substrate availability is not a likely explanation since free fatty acid release is similar or higher during exercise and following a meal in older compared to younger individuals (Jackson et al, 1982;Sial et al, 1996). Thus, in older individuals, it would appear as if the respiring tissue mass did not respond to increased free fatty acid availability by increasing fat oxidation.…”
Section: Effect Of Age On Fat Oxidationmentioning
confidence: 99%